2020
DOI: 10.1111/nmo.13848
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral modulation of gastrointestinal transit in mice by DN‐9, a multifunctional opioid/NPFF receptor agonist

Abstract: Background The nonapeptide DN‐9 functions as a multifunctional agonist to opioid and neuropeptide FF (NPFF) receptors and exhibits antinociceptive effects at the central and peripheral levels. Methods The effects of DN‐9 on small and colonic intestinal transit were evaluated using the upper gastrointestinal (GI) transit test and colonic bead expulsion assay, respectively. Opioid and NPFF receptor antagonists were used to investigate the mechanisms of DN‐9‐induced GI inhibition. Furthermore, the agonism of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…An increasing number of groups reported that mixed agonists/antagonists exhibited potent analgesia with reduced opioid-like side effects. A recent study suggests that the NPFF receptor agonist activity of DN-9 exhibits anti-opioid effects on the GIT and may help to reduce its constipation side effects . The present study showed that oral analogue 1 induced GIT inhibition at a dose of 2520-fold higher than the effective analgesic dose.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…An increasing number of groups reported that mixed agonists/antagonists exhibited potent analgesia with reduced opioid-like side effects. A recent study suggests that the NPFF receptor agonist activity of DN-9 exhibits anti-opioid effects on the GIT and may help to reduce its constipation side effects . The present study showed that oral analogue 1 induced GIT inhibition at a dose of 2520-fold higher than the effective analgesic dose.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these results suggest that the limited side effects of analogue 1 on constipation after p.o. administration are associated with its NPFF receptor agonism property, which is consistent with our recent study . Taken together, the reduced side effects of oral analogue 1 may be explained by its peripheral activities and multifunctional agonism of opioid and NPFF receptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations